Plateauing of Chinese female mid-career EFL teacher educators at regional teacher education universities. Issue 2 (4th March 2023) - Yan, Chunmei; He, Chuanjun; Guo, Xinjie; Wang, Jianyang
ABSTRACT: Professional development of teacher educators has received growing attention in recent years owing to their important role in preparing teachers for schools and universities, however, female-dominated mid-career EFL teacher educators in regional teacher education universities remain underexplored. This study examined 18 female experienced teacher educators' professional state, teaching beliefs and competence in a non-elite teacher education university. A combination of longitudinal observations, questionnaires, individual interviews, and official documents was employed to gather data. The results reveal the participants' plateauing indicated by their teaching-focused professional identity and the lack of personal and collective agency for professional development and organisational improvement. Personal and contextual factors were found to have caused their perceived lack of professional expertise, research inactivity in the pervading 'publish or perish' climate. The study yields implications to teacher educators, policymakers, and researchers in different educational and cultural contexts.